Target standards for hospital accreditation readiness on patient safety - Hazer Muzn; Aryan Sineen (Institute of Accounting Research and Novation (IARN), 2022)
According to the Indonesian Ministry of Health, certification is done to improve the quality of health services and boost public trust. According to a preliminary study completed in 2014, the accreditation status of the Jakarta Hajj Hospital still uses the 2009 accreditation, thus it is classified as expired because the three-year limit has passed. According to interviews. However, the implementation of the 2012 edition of the accrediting standard has been several months behind schedule. This study seeks to provide an overview of the organization's readiness to earn the 2012 edition of certification on patient safety goals. This study is qualitative in nature. Purposive sampling was used to choose research informants. In this study, the informants included one member of the SKP accrediting working group, two nurses, one pharmacy unit section, and two patients. To improve study validity, sources, techniques, and data are triangulated. The Patient Safety Goals are comprised of six objectives, according to the 2012 accreditation. Consisting of accurate patient identification, improved communication, greater drug safety, certainty of the correct location for the right procedure for the right patient, infection control, and a reduction in the danger of patients falling. The operator rarely noted the place of the procedure with an unique marker, and the hospital did not have records for monitoring and evaluating patients at risk of falling, according to the six guidelines. Meanwhile, for other goals, documentation and implementation have been completed. In order to reduce the risk of patients falling, the Jakarta Hajj Hospital must conduct more intense and convincing socialization about marking the site of procedures, as well as full monitoring and assessment papers